Konsep Pendekatan Behavior dalam Menangani Perilaku Indisipliner pada Siswa Korban Perceraian - Muchamad Agus Slamet Wahyudi (Edukasia Islamika, 2017)
This present study aims to investigate the concept of a behavioral approach in handling students’ indiscipline as a result of their parents’ divorce. It is one of approaches in guidance and counseling to change maladaptive behavior into adaptive one. The behavioral approach is deemed appropriate to deal with the students’ indiscipline at school so as to have good behavior. The students’ indiscipline is due to the students’ internal factor, including their family background in terms of a divorce case. A qualitative descriptive approach was employed in this field research. The results promote that if assessment was done, planning could be expanded on the process of counseling. It started from the contract of counseling and went up to relaxation, modeling, rewards and punishment, as well as a follow-up phase.